Sudden CEO vacancy and the long-run economic consequences - Lambertides, Neophytos (My University, 2009)
Purpose – The aim of this paper is to examine the long-term abnormal returns of firms that have experienced chief executive officer (CEO) succession. According to Chief Executive magazine, directors rank CEO succession as the second most important issue their firms face, the first being strategic planning. Design/methodology/approach – This study examines 202 CEO succession announcements. It utilizes two returns-generating models to calculate abnormal returns for two estimation windows of 200 trading days before and after the succession event. Findings – The results support the theory first developed by Guest (1962) that succession is an adaptive event. Specifically, this study shows that firms that experience a CEO change have positive abnormal returns, suggesting that new CEOs raise the firm performance. Moreover, this study shows that firms that experience CEO change due to CEO retirement improve firm performance in the post-succession period, whereas succession due to CEO sudden death or illness seems to have no direct effect on the long-term performance of these firms. Finally, this study provides strong evidence that outside successions help firms raise performance more than inside successions. Research limitations/implications – Like any empirical event-study, the validity of the results depends on the absence of confounding events. Future research could be to explore the relationship between the information content of the CEO succession announcement and the market reaction. Originality/value – This paper is believed to be the first attempt to empirically examine the relation between CEO turnover and long-term firm performance through the analysis of the successor's origin and of the force initiating the change, by using an event study methodology.
Keywords: Business performance; Chief executives; Financial performance; Succession planning